Feasibility of conductivity imaging using subject eddy currents induced by switching of MRI gradients - Oran, Omer Faruk; Ider, Yusuf Ziya (Magnetic resonance in medicine, 2017)
Purpose To investigate the feasibility of low‐frequency conductivity imaging based on measuring the magnetic field due to subject eddy currents induced by switching of MRI z‐gradients. Methods We developed a simulation model for calculating subject eddy currents and the magnetic fields they generate (subject eddy fields). The inverse problem of obtaining conductivity distribution from subject eddy fields was formulated as a convection‐reaction partial differential equation. For measuring subject eddy fields, a modified spin‐echo pulse sequence was used to determine the contribution of subject eddy fields to MR phase images. Results In the simulations, successful conductivity reconstructions were obtained by solving the derived convection‐reaction equation, suggesting that the proposed reconstruction algorithm performs well under ideal conditions. However, the level of the calculated phase due to the subject eddy field in a representative object indicates that this phase is below the noise level and cannot be measured with an uncertainty sufficiently low for accurate conductivity reconstruction. Furthermore, some artifacts other than random noise were observed in the measured phases, which are discussed in relation to the effects of system imperfections during readout. Conclusion Low‐frequency conductivity imaging does not seem feasible using basic pulse sequences such as spin‐echo on a clinical MRI scanner. Magn Reson Med 77:1926–1937, 2017. © 2016 International Society for Magnetic Resonance in Medicine